2002
DOI: 10.1124/dmd.30.3.349
|View full text |Cite
|
Sign up to set email alerts
|

The Alkaloid Rutaecarpine Is a Selective Inhibitor of Cytochrome P450 1A in Mouse and Human Liver Microsomes

Abstract: This article is available online at http://dmd.aspetjournals.org ABSTRACT:Rutaecarpine, evodiamine, and dehydroevodiamine are quinazolinocarboline alkaloids isolated from a traditional Chinese medicine, Evodia rutaecarpa. The in vitro effects of these alkaloids on cytochrome P450 (P450)-catalyzed oxidations were studied using mouse and human liver microsomes. Among these alkaloids, rutaecarpine showed the most potent and selective inhibitory effect on CYP1A-catalyzed 7-methoxyresorufin O-demethylation (MROD) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 25 publications
1
35
0
Order By: Relevance
“…observed with tolbutamide hydroxylase (CYP2C9), chlorzoxazone hydroxylase (CYP2E1), and nifedipine oxidase (CYP3A4) activities (Ueng et al, 2002). Similar to the CYP1A2 inhibitor furafylline, rutaecarpine preferentially inhibited 7-methoxyresorufin O-demethylase more than 7-ethoxyresorufin O-deethylase and had no effect on aryl hydrocarbon hydroxylase in 3-methylcholanthrene-treated mouse liver microsomes, indicating that rutaecarpine was a potent inhibitor of CYP1A2 in vitro.…”
Section: Zhou Et Al 58mentioning
confidence: 94%
See 1 more Smart Citation
“…observed with tolbutamide hydroxylase (CYP2C9), chlorzoxazone hydroxylase (CYP2E1), and nifedipine oxidase (CYP3A4) activities (Ueng et al, 2002). Similar to the CYP1A2 inhibitor furafylline, rutaecarpine preferentially inhibited 7-methoxyresorufin O-demethylase more than 7-ethoxyresorufin O-deethylase and had no effect on aryl hydrocarbon hydroxylase in 3-methylcholanthrene-treated mouse liver microsomes, indicating that rutaecarpine was a potent inhibitor of CYP1A2 in vitro.…”
Section: Zhou Et Al 58mentioning
confidence: 94%
“…Some alkaloids (e.g., rutaecarpine, evodiamine, and dehydroevodiamine) isolated from Evodia rutaecarpa inhibited 7-methoxyresorufin O-demethylase and 7-ethoxyresorufin O-deethylase (both are CYP1A) activities in mouse liver microsomes (Ueng et al, 2002). Rutaecarpine (Fig.…”
Section: J Alkaloidsmentioning
confidence: 99%
“…Microsomal cytochrome P450 (P450)-dependent monooxygenase plays a major role in the oxidative metabolism of xenobiotics including drugs and natural products (Guengerich, 1995;Hasler et al, 1999). Our previous reports demonstrated that rutaecarpine was a CYP1A2-selective inhibitor in human liver microsomes (Ueng et al, 2002b). Rutaecarpine was metabolized by rat liver microsomal enzymes to form 10-, 11-, 12-, and 3-hydroxyrutaecarpine (Ueng et al, 2005).…”
mentioning
confidence: 99%
“…In addition, Fructus evodiae (fruit of E. rutaecarpa) is also used for the treatment of headache, thoracicoabdominal pain, vomiting, colds, and reduced blood circulation (Fei et al, 2003). Pharmacological studies indicate that Rut has various bioactivities, such as causing vasodilatation by mechanisms of an endothelium-dependent manner coupled with the synthesis or release of nitric oxide (Wang et al, 1996), inhibiting vasoconstriction induced by anaphylaxis (Yu et al, 2005), inducing positive inotropic and chronotropic actions (Kobayashi et al, 2001), protecting the myocardium mediated by calcitonin gene-related peptide (Hu et al, 2002;Yi et al, 2004), increasing intracellular Ca 2ϩ concentration in endothelium (Wang et al, 1996), suppressing platelet plug formation in mesenteric venules (Sheu et al, 2000), inhibiting prostaglandin production in RAW264.7 macrophages (Woo et al, 2001), relaxation of rabbit and human internal anal sphincter (Jiang et al, 2000), gastroprotective effect against injury induced by aspirin and stress (Wang et al, 2005), anti-Helicobacter pylori (Tominaga et al, 2002), blockade of delayed rectifier K ϩ current in NG108-15 neuronal cells (Wu et al, 2001), inhibiting cytochrome P450 in human liver microsomes (Ueng et al, 2002(Ueng et al, , 2006Iwata et al, 2005), and inhibition of COX-2 (Moon et al, 1999).…”
mentioning
confidence: 99%